Building and applying a scale of educational supervision patterns for physical education supervisors in the Diyala Education Directorate - Abed Al-Tameemi, Israa Jasim; Ahmed, Maysa Nadeem (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The aim of this study was to build and apply a scale of educational supervision patterns for supervisors in the Directorate of Education in Diyala, as well as to identify the level of educational supervision patterns of supervisors. As for the study methodology, the researchers used the descriptive approach in the survey method. The research community was represented by the educational supervisors (N = 80) of the Directorate of Education in Diyala, for the academic year 2021/2022. As for the main application sample, 67 supervisors with a percentage of 83.75% were chosen randomly, 3 supervisors with a percentage of 3.75% were chosen randomly for the pilot experiment sample, and 10 supervisors with a percentage of 12.5% were chosen for the application sample. The data were processed through the Statistical Package for the Social Sciences (SPSS). Our study results showed that the educational supervisors had a good level of educational supervision patterns. The current scale was considered as an important tool for detecting the level of educational supervision patterns in all its aspects. Based on our study results, we recommend that this scale is used in all education directorates in Iraq and that similar studies are conducted on this scale in other countries.